Remembering and forgetting the Kalunga Project: popular music and the construction of identities between Brazil and Angola. Issue 1 (2nd January 2016) - de Castro, Maurício Barros
Abstract : Kalunga Project was a mission of 65 Brazilian musicians, artists, producers, motion-pictures directors, and journalists that travelled to Angola in 1980, when the country was in a civil war. The invitation was made by the Angolan Government, and the caravan went through Luanda, Benguela, and Lobito, cities where the musicians performed shows, during a 12-day travel, characterized by a strong political connotation. The Kalunga Project happened without the official recognition of the Brazilian Government and it was not divulged by the press at that time, due to the censorship. The event had a clear political position at the international scenario polarized by the cold war. It was not only about supporting the Angolan people, but also the block of the socialist countries, from what Angola was part, as an allied country of the USSR and Cuba. At this time, Brazil was living a slow process of redemocratization that had begun with the Amnesty Law, in 1979. The mission reveals a postcolonial dialogue between Brazil and Angola of both musical and political dimensions. The Kalunga Project is also important in highlighting the transnational connections between the performance of Brazilian samba and Angolan semba, affording an insight into the construction of identities in the Black Atlantic